Analisis Komoditas Emas dengan Konsep Riba dalam Perspektif Usul Fikih - Syahrir, M. Dzul Fadli; M. Wahyuddin Abdullah; Khaerul Aqbar (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2021)
This research aimed to reveal gold whose function as a commodity has fallen out of the category aá¹£naf al-riba or not. This research was prepared using the normative method or reference study by examining classical Ulama books. The results of this study concluded that gold which functions as a commodity is not excluded from the aá¹£nÄf al-riba category so that the transaction must pay attention to the rules of usury, including that it cannot be bought and sold without cash.